Criminology and Fundamental Rights : The Selected Combat Slavery to Contemporary - Matheus Felipe de Castro; Marcio Cristiano de Gois (Revista Brasileira de Direitos e Garantias Fundamentais, 2016)
The article is subject to study criminology and fundamental rights. The problem of research focuses on analyzing the selected combat contemporary slavery. Justified the issue because of still thousands of people are subjected to slave labor in Brazil. The purpose is to study, promote discussion of this important law. Analysis of the material collected part of a Marxist and critical theoretical framework. The method used was deductive and the work is divided into two parts. a) the setting of contemporary slavery; b) the recognition of slavery from the criminology.